FGF2 and IL-1β - explorers of unconventional secretory pathways at a glance - Pallotta, Maria Teresa; Nickel, Walter (Journal of cell science, 2020)
Skip to Next Section - Fibroblast growth factor 2 (FGF2) and interleukin 1β (IL-1β) were among the earliest examples of a subclass of proteins with extracellular functions that were found to lack N-terminal secretory signal peptides and were shown to be secreted in an ER- and Golgi-independent manner. Many years later, a number of alternative secretory pathways have been discovered, processes collectively termed unconventional protein secretion (UPS). In the course of these studies, unconventional secretion of FGF2 and IL-1β were found to be based upon distinct pathways, mechanisms and molecular machineries. Following a concise introduction into various pathways mediating unconventional secretion and transcellular spreading of proteins, this Cell Science at a Glance poster article aims at a focused analysis of recent key discoveries providing unprecedented detail about the molecular mechanisms and machineries driving FGF2 and IL-1β secretion. These findings are also highly relevant for other unconventionally secreted cargoes that, like FGF2 and IL1β, exert fundamental biological functions in biomedically relevant processes, such as tumor-induced angiogenesis and inflammation.